Firm heterogeneity and wages in unionised labour markets : theory and evidence - Bastos, Paulo (2009)
In many countries wages are set in two stages, where industry-level collective bargaining is followed by firm-specific arrangements determining actual paid wages as a mark-up on the industry wage floor. What explains the wage set in each of these stages? In this paper we show that both the industry wage floor and the average wage cushion are systematically associated with the degree of firm heterogeneity in the industry: The former (latter) is negatively (positively) associated with the productivity spread. Furthermore, since the response of the wage floor dominates that of the wage cushion, workers in more heterogeneous industries tend to get lower actual paid wages. These conclusions are reached in a model of Cournot oligopoly with firm productivity heterogeneity and a two-tiered wage setting system. They are then confirmed by administrative data covering virtually all workers, firms and collective bargaining agreements of the Portuguese private sector for the period 1991–2000.